Quantitative solid-phase assay to measure deoxynucleoside triphosphate pools - Landoni, Juan Cruz (Biol Methods Protoc, 2018)
deoxynucleoside triphosphate (dNTPs) are the reduced nucleotides used as the building blocks and energy source for deoxyribonucleic acid (DNA) replication and maintenance in all living systems. They are present in highly regulated amounts and ratios in the cell, and their balance has been implicated in the most important cell processes, from determining the fidelity of DNA replication to affecting cell fate. Furthermore, many cancer drugs target biosynthetic enzymes in dNTP metabolism, and mutations in genes directly or indirectly affecting these pathways that are the cause of devastating diseases. The accurate and systematic measurement of these pools is key to understanding the mechanisms behind these diseases and their treatment. We present a new method for measuring dNTP pools from biological samples, utilizing the current state-of-the-art polymerase method, modified to a solid-phase setting and optimized for larger scale measurements.